Development of STREAM-Based Science E-Module for Junior High School/MTs on the Topic of Magnetism - Aryani, Sri; Diniya, Diniya; Zarkasih, Zarkasih (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Teaching materials can assist teachers in achieving learning objectives. However, teaching materials integrated with Quranic verses in science learning are still limited. This research aims to produce products in the form of electronic teaching materials (e-modules) based on STREAM (Science, Technology, Religion, Engineering, Art and Mathematics) on the topic of magnetism. The existence of STREAM-based and attractively presented e-module products is expected to support students' self-learning. Through the research and development (R&D) method, reseachers adopt the Borg and Gall R&D method, which is limited to the fifth step, namely the initial main product revision. The results showed 85% valid in terms of teaching materials, 95% valid in terms of preparation of teaching materials, 86% valid in terms of integration of science in the Quran and 95% declared practical. Thus, it can be concluded that the e-module-based STREAM is valid and practical to implement during science learning on the topic of magnetism. The integration of Qur’an verses in e-modules helps connect science with religious values and expects to provide contextual learning experiences for junior high school students. This e-module-based STREAM for junior high school science e-module on the topic of magnetism presents an innovative approach in STREAM-based learning and improves the quality and efficiency of the teaching-learning process. The integration of the latest technology is expected to facilitate interactive, collaborative and effective learning experiences, thus improving significant learning outcomes.